Pelatihan Simulasi Jaringan Sederhana Topologi Hybrid Menggunakan Cisco Packet Tracer 7.3 - Amelia Anggraini; Indah Rahma Sari; Bella Paramita; Anggoro Aryo Pramuditho; Mahmud Mahmud (Yayasan Literasi Sains Indonesia, 2025)
The development of information technology requires basic skills in understanding and managing computer networks, especially among students and the general public. However, hardware limitations are often an obstacle in the process of learning networks directly. To overcome this, this training activity was held with the aim of providing an understanding and basic skills regarding computer network simulation using hybrid topology through the Cisco Packet Tracer 7.3 application. The training method uses the Participatory Action Research (PAR) approach which actively involves participants in the process of identifying problems, planning, implementing, and evaluating. The results of the training showed that participants experienced an increase in understanding of network topology and were able to build hybrid network simulations independently. In addition, the use of Cisco Packet Tracer has proven effective as an interactive and applicable learning tool. With this training, it is hoped that participants will have the initial provisions to develop competencies in the field of computer networks, both for academic and professional needs. This activity also opens up opportunities for further training on a more complex and in-depth scale.